Spermidine‐cross‐linked hydrogels as novel potential platforms for pharmaceutical applications. Issue 8 (11th June 2013) - López‐Cebral, Rita; Paolicelli, Patrizia; Romero‐Caamaño, Vanessa; Seijo, Begoña; Casadei, Maria Antonietta; Sanchez, Alejandro
Abstract: Endogen polyamines are known to be molecules of high biological value. Herein, a new generation of physical hydrogels was developed through the mild ionotropic gelantion technique, using the endogen polyamine spermidine as a physical cross‐linker. The main negatively charged polymer of the hydrogel is the natural polysaccharide gellan gum. Optionally, interesting endogen molecules, such as chondroitin sulfate and albumin, can be included as part of the formulation. These new hydrogels were characterized and the influence of the different components on their final properties was carefully analyzed, ultimately demonstrating the possibility to modulate these properties as well as the system's versatility in terms of composition. On the contrary, in vitro cell studies showed the absence of cytotoxicity of these hydrogels. Finally, the in vitro ‐release profiles obtained for different model molecules evidenced the potential of these systems as novel drug delivery platforms. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2632–2643, 2013